(untitled) - Best, Constance (Washington, 2001)
The book identifies the major threats to private forests in the United State, considers barriers to conservation, outlines the available tools and programs for promoting conservation, presents a "road map" to guide collective efforts for the conservation of private forests and their native biodiversity
Keywords: Private forests,Forest conservation,Forest management,Forest policy; United States,United States,United States,United States